HADIS QUDSI DALAM PERSPEKTIF PSIKOLOGI TRANSPERSONAL - Idris, Abdul Fatah (Jurnal THEOLOGIA, 2018)
Hadith Qudsi is a Hadith which its meaning and text come from the Prophet Muhammad SAW. The Koran and the Hadith also come from the revelation internally (from deep heart of the Prophet) and nonverbal (not words form). To understand the meaning hadith qudsi, the author uses the revelation theory through transpersonal psychology. The study found explanations that there are three categories of prophet speech: the Koran, hadith Nabawi, and hadith qudsi. These all come from the inspiration of Ilahi (the revelation of God), not in the form words or language. Then, the prophet created human language (texts) and applied them in his daily life.